Combinatorial Image Analysis 15th International Workshop, IWCIA 2012, Austin, TX, USA, November 28-30, 2012, Proceedings - Barneva, Reneta P.; Brimkov, Valentin E.; Aggarwal, Jake K. (Image Processing, Computer Vision, Pattern Recognition, and Graphics ;, 2012)
This volume constitutes the refereed proceedings of the 15th International Workshop on Combinatorial Image Analysis, IWCIA 2012, held in Austin, TX, USA in November 2012. The 23 revised full papers presented were carefully reviewed and selected from numerous submissions. The topics covered include digital geometry, combinatorics in digital spaces, digital curves and surfaces; digital topologyl grammars, transformation, applications; grammars and models in image analysis; picture transformations, morphologic operations, image segmentation; and discrete tomography, applications.